International tourism development in the context of increasing globalization risks: On the example of Ukraine's integration into the global tourism industry - Yurii Kyrylov; Viktoriia Hranovska; Viktoriia Boiko; Aleksy Kwilinski; Liudmyla Boiko (Journal of Risk and Financial Management, 2020)
Today, international tourism is one of the most affected sectors of the economy due to the global COVID-19 pandemic. The main purpose of this article is to analyze current trends and identify prospects for the international tourism development in the context of increasing globalization risks in the world, using the example of Ukraine's integration into the global tourism industry, as Ukraine is located in the centre of Europe and belongs to a number of countries with developing economies, and has the potential to expand its tourism industry, which may be of interest to the international scientific community in terms of overcoming the bifurcation point of its economic development. Analyzing the tourism industry, as one of the most progressive sectors of the world economy, we used general scientific and special research methods (abstract-logical, statistical, systemic analysis and synthesis, abstract-theoretical, and correlation-regression analysis). The paper analyzes major indexes of international tourism development in the modern globalized world and details the risks emerging during the global COVID-19 pandemic. It examines the global dynamics of tourism flows, where France, Spain, and the USA are unquestionable leaders. The study considers foreign exchange earnings of international tourism and the industry contribution to the gross domestic product of countries being an essential component of national budgets. Based on the study conducted, there were developed reliable forecast models for the tourism industry development in the countries under research. These models will provide an opportunity to generate reliable forecasts, which will allow timely identification of potential threats and making effective decisions to address them. At the same time, the issues of managing information support of economic entities in the field of international tourism need to be further developed in order to reduce risks.
Keywords: 330; international tourism; globalization risks; global tourism trends; tourism industry; information technology; travel